Handel, Puccini, Strauss, Poulenc, Brown, and Gealt an exploration of song. - Frye, Randall William (Kansas State University, 2014)
This Master’s Report contains extended program notes on the works performed on a graduate rectial of music for a Baritone. The text includes biographical information on each composer and an analysis of each piece performed. Text translations are included in the body of the discussions. The pieces discussed are Handel’s “See The Raging Flames Arise,” from Joshua, Poulenc’s Le Bestiaire, Strauss’s Zueignung, Nichts and Cäcilie, Puccini’s “Questo amor, vergogna mia,” from Edgar, Jason Robert Brown’s Moving Too Fast, The Next Ten Minutes, The River Won’t Flow and She Cries and lastly Jonathon Reid Gealt’s September of ’92. The graduate recital was given in partial fulfillment of the requirements for the Master of Music degree in vocal performance on April 7, 2014. It was performed in All Faiths Chapel at Kansas State University. It featured the piano talents of Amanda Arrington, Paul Meissbach and Norma Roozeboom, the vocal talents of Reginald Pittman, Elise Poehling and Patricia Thompson, and the insrumental talents of Nolan Groff and Craig Archer.
Keywords: Le Bestiaire; See the Raging Flames Arise; Richard Strauss; Jason Robert Brown; Questo amor, vergogna mia; Jonathan Reid Gealt; Music (0413)